2023
DOI: 10.1021/acscatal.3c01217
|View full text |Cite
|
Sign up to set email alerts
|

Surface Synergetic Effects of Ni–ReOx for Promoting the Mild Hydrogenation of Furfural to Tetrahydrofurfuryl Alcohol

Abstract: Ni−ReO x bimetallic catalysts (Ni−ReO x /TiO 2 ) were prepared through a successive impregnation method, which is extremely active in furfural (FAL) hydrogenation to tetrahydrofurfuryl alcohol (THFOL) under mild reaction conditions. For instance, high FAL initial reaction rate (439.4 mmol/g -Ni /h) and THFOL formation rate (80.4 mmol/g -Ni /h) were achieved over Ni−5ReO x /TiO 2 , which are 13.2 and 6.6 times higher than those of Ni/TiO 2 , respectively. The unique catalyst reactivity derives from rich Lewis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Nitrogen adsorptiondesorption assays were conducted to assess the catalyst samples' surface area and pore size distribution. As Figure 3B demonstrates, all samples show characteristic type IV isotherms and H3 hysteresis loops, indicative of mesoporous structures [33]. Observations indicate a relatively uniform pore size distribution in the samples (Figure 3C), particularly for Ru/TNSTs-4, which demonstrates a complex pore structure combining microporous and mesoporous characteristics.…”
Section: Resultsmentioning
confidence: 87%
“…Nitrogen adsorptiondesorption assays were conducted to assess the catalyst samples' surface area and pore size distribution. As Figure 3B demonstrates, all samples show characteristic type IV isotherms and H3 hysteresis loops, indicative of mesoporous structures [33]. Observations indicate a relatively uniform pore size distribution in the samples (Figure 3C), particularly for Ru/TNSTs-4, which demonstrates a complex pore structure combining microporous and mesoporous characteristics.…”
Section: Resultsmentioning
confidence: 87%
“…Lin et al. found that the strong electronic interaction between Ni and ReO x enabled the catalyst to exhibit good hydrogenation activity [80] . As a strong electron donor of Ni, ReO x is conducive to improving the stability of metal Ni on the TiO 2 surface.…”
Section: Conversion Of Ff To Renewable Value‐added Chemicalsmentioning
confidence: 99%
“…Newly, the thermochemical conversion of platform substances derived from lignocellulosic biomass such as furfural (FAL), 5-hydroxymethylfurfural (HMF), and levulinic acid (LA) though the hydrogenation and hydrogenolysis reactions under pressurized H 2 system have been widely investigated using heterogenous catalysts. [1][2][3][4][5][6][7] Among the platform substances, the HMF derived from cellulose fraction via hydrolysis and dehydration processes could be utilized as a useful feedstock for the production of biofuels and biochemicals based on the modern biorefinery concept. In thermochemical routes under H 2 atmosphere, the valuable multipurpose compounds of 2,5-bis(hydroxymethyl)furan (BHMF) 2,5-dimethyltetrahydrofuran (DMTHF) 5-methylfurfuryl alcohol (MFA), 5-methylfurfural (MF), and 2,5-dimethylfuran (DMF) could be generated from the hydrogenation of C=O bond and hydrogenolysis of CÀ OH bond of HMF using heterogenous non-noble and noble catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Newly, the thermochemical conversion of platform substances derived from lignocellulosic biomass such as furfural (FAL), 5‐hydroxymethylfurfural (HMF), and levulinic acid (LA) though the hydrogenation and hydrogenolysis reactions under pressurized H 2 system have been widely investigated using heterogenous catalysts [1–7] . Among the platform substances, the HMF derived from cellulose fraction via hydrolysis and dehydration processes could be utilized as a useful feedstock for the production of biofuels and biochemicals based on the modern biorefinery concept.…”
Section: Introductionmentioning
confidence: 99%